Knowledge, Attitudes, And Practices Regarding Chronic Kidney Disease Among At-Risk Populations - Yulianti, Melli; Mahmud, Salsa Nafarila; Nurdina, Gina; Herdiman, Herdiman (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2025)
Background: Chronic kidney disease (CKD) is a growing global health problem with a steadily increasing prevalence. CKD substantially affects individuals’ quality of life and imposes a significant economic burden on healthcare systems, particularly at advanced stages requiring long-term treatment. Community knowledge, attitudes, and practices (KAP) related to CKD risk factors play a critical role in disease prevention and early control. Objective: This study aimed to analyze the relationship between demographic characteristics, risk factors, and knowledge, attitudes, and practices related to CKD prevention among at-risk populations. Methods: A quantitative descriptive study with a cross-sectional design was conducted among 119 individuals from at-risk groups in the Pasirkaliki Public Health Center working area, Bandung. Participants were selected using convenience sampling. Data were collected using the CKD Screening Index questionnaire. Statistical analysis included frequency distribution, independent t-tests, and one-way analysis of variance (ANOVA). Results: Overall, respondents demonstrated limited CKD knowledge (mean = 9.23), positive attitudes (mean = 58.44), and relatively healthy preventive practices. Knowledge was significantly associated with age (p = 0.001), educational level (p < 0.001), and occupation (p = 0.003). Attitudes were significantly related to gender (p = 0.034) and age (p = 0.017), while preventive practices were associated with age (p = 0.003) and education (p = 0.001). Conclusion: Demographic characteristics significantly influence community knowledge, attitudes, and practices regarding CKD prevention. Targeted and intensified health promotion strategies that consider these factors are essential to strengthen CKD prevention efforts.